Multiscale Hierarchical Architecture‐Based Bioactive Scaffolds for Versatile Tissue Engineering. Issue 13 (13th April 2022) - Ma, Hongshi; Yang, Chen; Ma, Zhenjiang; Wei, Xiaoyue; Younis, Muhammad Rizwan; Wang, Hanbo; Li, Wentao; Wang, Zhiyong; Wang, Wenhao; Luo, Yongxiang; Huang, Peng; Wang, Jinwu
Abstract: Artificial construction from tendon to bone remains a formidable challenge in tissue engineering owing to their structural complexity. In this work, bioinspired calcium silicate nanowires and alginate composite hydrogels are utilized as building blocks to construct multiscale hierarchical bioactive scaffolds for versatile tissue engineering from tendon to bone. By integrating 3D printing technology and mechanical stretch post‐treatment in a confined condition, the obtained composite hydrogels possess bioinspired reinforcement architectures from nano‐ to submicron‐ to microscale with significantly enhanced mechanical properties. The biochemical and topographical cues of the composite hydrogel scaffolds provide much more efficient microenvironment to the rabbit bone mesenchymal stem cells and rabbit tendon stem cells, leading to ordered alignment and improved differentiation. The composite hydrogels markedly promote in vivo tissue regeneration from bone to tendon, especially fibrocartilage transitional tissue. Therefore, such calcium silicate nanowires/alginate composite hydrogels with multiscale hierarchical structures have potential application for tissue regeneration from tendon to bone. This work provides an innovative strategy to construct multiscale hierarchical architecture‐based scaffolds for tendon/bone engineering. Abstract : Bioinspired calcium silicate (CS) nanowires/alginate composite hydrogels with multiscale hierarchical structures are prepared by 3D printing technology and mechanical stretch post‐treatment in a confined condition. Such composite hydrogels possess bioinspired reinforcement architectures with significantly enhanced mechanical properties, facilitate the ordered alignment and differentiation of stem cells, and promote tissue regeneration from bone to tendon.